0050 Shift Work And Symptoms Of Anxiety And Depression Among Chinese Practice Nurses: A Prospective Study. (27th April 2018) - Chen, X; Fan, F; Shi, X
Abstract: Introduction: Shift work is associated with sleep problems and psychological health outcomes. The main aim of the present study was to investigate shift work-related sleep problems change in depression as well as anxiety following a transition to a shifts work schedule using a longitudinal design. Methods: This is a longitudinal study with two waves of data collection. A total of 664 nurses(all females;17.83 ± 1.56 years)were assessed at baseline, prior to commencing shift work. They were re-assessed during the follow-up sessions within the first half a year of shift work exposure after approximately 3 months of rotating shift work. Participants reported demographic characteristics and whether suffering Insomnia. They also completed the Patient Health Questionnaire, the Generalized anxiety disorder-7, Composite Morningness Questionnaire, Circadian Type Inventory-11, Epworth Sleepiness Scale and some questions concerning shifting work. Results: The prevalence of depression at follow-up was 10.4% and anxiety was 16%.Logistic regression analyses showed signiﬁcant risks of being depression at follow-up and the following variables measured at baseline after controlling the baseline depression, demographic characteristics and other items about shift work: languidity (OR = 1.15, 95% CI = 1.01–1.30), Insomnia symptoms(OR = 3.20, 95% CI = 1.37–7.47) and sleepiness(OR = 1.14, 95% CI = 1.03–1.26); as well, Insomnia symptoms(OR =3.35, 95% CI = 1.69–6.97) and sleepiness(OR = 1.19, 95% CI = 1.10–1.30) may associated with a signiﬁcantly risk of anxiety at follow-up. Conclusion: The prevalence of depression and anxiety after shifting work were relatively high among these shift nurses. Individuals with shift work-related sleep problems: languidity, insomnia and sleepiness were more suffering depression. Those who reported insomnia and sleepiness symptoms were more experiencing anxiety. This suggests that shift work-related sleep problems may exacerbate individual depression and anxiety. Support (If Any): no